2018
DOI: 10.1007/s10815-018-1287-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perinatal outcomes following frozen embryo transfer cycles using autologous versus donor oocytes in women 40 to 43 years old: analysis of SART CORS data

Abstract: Singletons resulting from d-FET are at increased risk for perinatal morbidity. However, the risk was diminished in single blastocyst transfer cycles. Our study supports the current American Society for Reproductive Medicine (ASRM) guidelines of transferring a single blastocyst in d-FET cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous studies suggested that donor sperm or oocyte embryo transfer is associated with a risk for preeclampsia in frozen cycles (40,41). Furthermore, donor sperm embryo transfer is associated with an increased risk of SGA, and donor oocyte embryo transfer is associated with a higher risk of preterm births and LBW (41)(42)(43)(44)…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that donor sperm or oocyte embryo transfer is associated with a risk for preeclampsia in frozen cycles (40,41). Furthermore, donor sperm embryo transfer is associated with an increased risk of SGA, and donor oocyte embryo transfer is associated with a higher risk of preterm births and LBW (41)(42)(43)(44)…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that even singleton pregnancies conceived after IVF-ET are more likely to develop prematurity, gestational hypertension, placental abruption, low birth weight and intrauterine growth retardation [6][7][8][9][10]. The risk of adverse outcomes originating from suboptimal placentation in pregnancies after IVF-ET is significantly greater than that in spontaneously conceived pregnancies [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This positive trend is due to more appropriate embryo transfer strategies, milder ovarian stimulation, laboratory technological advances, and improved culture media [5]. However, even in singleton pregnancy, after adjustment for maternal confounding factors, the risk of multiple adverse outcomes during the perinatal period, including miscarriage, preterm birth, small for gestational age, low birth weight and gestational hypertension, are higher in IVF-ET pregnancies than in spontaneously conceived pregnancies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%